Corporate social responsibility accounting for arising issues. Issue 4 (6th November 2017) - Weber, Florian; Larsson-Olaison, Ulf
Abstract : Purpose: Arising societal issues challenge corporate social responsibility. The purpose of this paper is to analyze how corporations account for arising issues under different institutional settings: the stakeholder oriented corporate governance model of Germany is hypothesized to produce a different response than the more state dominated Swedish welfare model. Design/methodology/approach: This paper takes the reported CSR response of the largest corporations in Germany and Sweden, in relation to the 2015 European refugee crisis, as its case. In total, 157 annual reports are investigated by means of text analysis for statements in relation to the European refugee crisis. Findings: Empirically, German corporations are more prone to communicate on this emerging issue, and deploying corporate resources to an emerging societal crisis. Based on that finding, this study concludes that the German model is more in line with international CSR-discourse than the Swedish. Research limitations/implications: This study has implications for institutional theory perspectives on CSR accounting-related issues. By comparing two economies that would be characterized as "coordinated market economies" a somewhat different set of topics becomes apparent. Further considering country context could be useful when expanding the debate on CSR accounting. Originality/value: This study is the first to empirically investigate corporate diplomacy with regard to the European refugee crisis. Besides others, corporations are important societal players. Therefore, corporations bear both, the obligation to deal with arising issues and the potential to participate in public opinion-forming with regard to those issues.